Evolution of Clinical Trials in Ovarian Cancer Management over the Past 20 Years: Never Settle Down, Always Go Beyond. (7th October 2021) - De Felice, Francesca; Vertechy, Laura; Giudice, Elena; Ergasti, Raffaella; Boccia, Serena; Fagotti, Anna; Scambia, Giovanni; Marchetti, Claudia
Abstract : Purpose . A practice synthesis of available evidence-based medicine data in ovarian cancer (OC), aiming to provide directions for future research. Materials and Methods . We performed a systematic review. PubMed was searched for relevant OC trials between January 2000 and December 2019. Results . Out of 865 references screened, 199 trials were found eligible for inclusion. Most trials were multicenter (83.9%). There was a trend reduction in the number of patients enrolled/per study over the years. Studies testing targeted/biological therapies dominated the second decade (60 trials in 2010–2019 versus 2 trials in 2000–2009). The proportion of trials with positive survival and clinical outcomes significantly increased from 23.8% in early 2000s to 54.1% in the last 5 years. Trials with histology/molecular biomarker criteria were more likely to meet progression-free survival endpoint than those without these selection criteria (69.2% versus 32.6%). Conclusion . This systematic review suggests a trend of increased positive studies, mainly linked to precision medicine.